Integrating energy literacy into science education: a comprehensive systematic review - Nik Abdul Majid, Nik Aida Mastura; Osman, Kamisah; Siok Yee, Tan (Institute of Advanced Engineering and Science, 2025)
Energy literacy is vital for preparing future generations to tackle global energy issues and advance sustainable development. However, integrating energy literacy into science education faces challenges due to diverse pedagogical approaches and educational contexts. This systematic literature review synthesizes current research to identify effective strategies for embedding energy literacy in science education. By employing advanced search techniques and preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, a thorough search across Scopus, Web of Science, and ERIC databases yielded 30 relevant studies meeting inclusion criteria. Findings indicate that interdisciplinary approaches, hands-on experiments, and innovative teaching tools like virtual and augmented reality (VR-AR) effectively enhance students’ understanding and attitudes toward energy, particularly renewable energy. Notably, project-based learning and science, technology, engineering, and mathematics (STEM) integration significantly improve problem-solving skills and creativity. Despite these positive outcomes, challenges such as high cognitive load in interdisciplinary courses and the need for ongoing teacher training persist. The review concludes that standardized curricula and professional development programs are necessary to further support teachers. Future research should focus on longitudinal studies to assess the long-term impact of these educational interventions and explore scalable models for diverse educational settings. This review provides valuable insights for educators, policymakers, and researchers aiming to enhance energy literacy through science education.